Nobody knows you : how to fix your biggest challenge to scale your business - Humblet, Michael, ....- (Brugge : Die Keure, 2020)
The biggest hurdle between you and your plans for growth is this: nobody knows you. This is true if you're a freelancer, an employee, an executive, even a company founder. You may be going all out with your company brand, but you've neglected to hone your own. But the first thing your business needs to grow, is you. If you feel like there is way more potential than you are currently leveraging, this book is for you. It is for those wanting to scale their business. For those sitting on a great idea with nowhere to go next. For those experts looking for ways to share the knowledge. For those corporate execs who need to find the next competitive edge. And for those who simply want to find another career path. It is time your prospects, future customers, investors or employer got to know you. Fix this basic flaw of remaining under the radar. With the insights in this book, you'll set out your strategy and create content. Not just any content, but content that matters. Content that makes you tick and brings you the right contacts. Build your thought leadership and leverage it as a mechanism to scale your business—starting with yourself.
Keywords: Ondernemingen ; zelfontplooiing